Hukum Keluarga Islam di Arab Saudi: Dinamika, Tantangan, dan Arah Reformasi - Hany Khairunnisa Kobat; Maila Lidinia; Nesi Alia Putri; Alray Habib Azmi; Muhammad Abrar; Aulil Amri (al-Battar: Jurnal Pamungkas Hukum, 2025)
This journal aims to specifically examine Islamic Family Law in Saudi Arabic, including history, legal sources, and basic matters such as marriage, inheritance, divorce, wills adoption, and waqf. The method used is a literature study of Islamic legal literature and regulation and schools of tought based on the Al-Qur’an and Hadist. The result of study indicate that Arab Islamic Family Law has undergone significant changes, especially since the establishment of the kingdom of Sa’ud Ibn Muhammad Ibnu Mukran. However, challenges still exist in society, public understanding, and critism of sereval provisions that are considered gender biased. Legal reform and contextualization are still needed so that Islamic family law can provide more equitable justice for all Muslims In Saudi Arabia. Local people tend to follow the Imam Hambali and Sunni schools of tought, this is why the are differences in every challenge that occurs in society.the exictence of regulation on marriage provides certainty, maintains sharia so that it is maintained, creates order, and maintains stability in the household. This reflects the existing values that remain in sync with the very strong and diverse Saudi Arabian culture, especially regarding the rights and obligations of men and women in building a household. The legal system used still uses both traditional and modern legal system.